Chīwit phūak rao chāo thalē : Kāmō̜i, ʻŌ̜lāng Mō̜kǣn, Kāmī, ʻŪrak Lāwōi = We, the sea people - Narưmon Hinchīranan ʻArunōthai (Sathāban Wičhai Sangkhom, Čhulālongkō̜n Mahāwitthayālai, 2010)
Children's book on the ways of life, tradition, and culture of the Moken, Southeast Asian people, in Thailand.